The Antimicrobial Activity of Two Marine Red Algae Collected from Algerian West Coast - Souhila Saim; Fatima Sahnouni; Djilali Bouhadi; Soumia Kharbouche (Shiraz University of Medical Sciences, 2021)
In this present study, extracts of two marine red algae (Asparagopsis taxiformis, Hypnea musciformis), harvested from Algerian West Coast (Oran), were investigated for their antimicrobial activity against Human pathogenic bacteria including antibiotic-resistant organisms and three fungi. Their antimicrobial activities from crude methanolic extracts were evaluated by using the paper disc agar diffusion method at different concentrations (0.5 to 2mg/ml). Methanolic extract of A. taxiformis showed highest antibacterial activity compared to that of H.musciformis. This activity was dependent of the used concentration of methanolic extracts. Methanolic extract of A. taxiformis elicited remarkable antimicrobial activity against all Human pathogenic bacteria except Salmonella sp. (Sa10) and Serratia sp (Se11). However, this extract showed moderate antifungal activity against Candida albicans and Penicellium sp. On the other hand, results obtained show that methanolic extract of H. musciformis exhibit a low activity which was effective only at 02 and 1.5 mg/ml. However, for its antifungal activity, a potent activity against C.albicans, Aspergillus sp. and Penicellium sp. was recorded. The present finding confirms that marine algae can be further studied and used as a possible source of antimicrobial compounds in the medical field.